2019
DOI: 10.1371/journal.pone.0223066
|View full text |Cite
|
Sign up to set email alerts
|

CT-perfusion in peripheral arterial disease – Correlation with angiographic and hemodynamic parameters

Abstract: ObjectiveThe purpose of this study was the assessment of volumetric CT-perfusion (CTP) of the lower leg musculature in patients with symptomatic peripheral arterial disease (PAD) of the lower extremities, comparing it with established angiographic and hemodynamic parameters.Materials and methodsThirty-five consecutive patients with symptomatic PAD of the lower extremities requiring interventional revascularization were assessed prospectively. All patients underwent a CTP scan of the lower leg, and hemodynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Recapitulating our results, we have shown that CTP values obtained in calf musculature, which represents the anatomic substrate for the clinical hallmark of critical limb ischemia, i.e. claudication, might represent an appropriate overview of local PAD [10]. CTP accounts for physiological compensation mechanisms of the body and functional collateralisation.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…Recapitulating our results, we have shown that CTP values obtained in calf musculature, which represents the anatomic substrate for the clinical hallmark of critical limb ischemia, i.e. claudication, might represent an appropriate overview of local PAD [10]. CTP accounts for physiological compensation mechanisms of the body and functional collateralisation.…”
Section: Discussionsupporting
confidence: 72%
“…1 a Blood flow before and after revascularisation. b Blood volume before and after revascularisation of the dependent tissue, and this complex situation is not represented by simple, large vessel-based parameters [10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations